2017
DOI: 10.1016/j.jalz.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β synaptotoxicity is Wnt‐PCP dependent and blocked by fasudil

Abstract: IntroductionSynapse loss is the structural correlate of the cognitive decline indicative of dementia. In the brains of Alzheimer's disease sufferers, amyloid β (Aβ) peptides aggregate to form senile plaques but as soluble peptides are toxic to synapses. We previously demonstrated that Aβ induces Dickkopf-1 (Dkk1), which in turn activates the Wnt–planar cell polarity (Wnt-PCP) pathway to drive tau pathology and neuronal death.MethodsWe compared the effects of Aβ and of Dkk1 on synapse morphology and memory impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 49 publications
6
101
0
1
Order By: Relevance
“…Aβ synaptoxicity is Dkk1-dependent 12 , 24 and also appears to be APP-dependent 25 . The results described above show that APP enhances the effects of Dkk1, changing the balance of Wnt signalling away from the Wnt-β-catenin pathway and towards Wnt-PCP signalling.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Aβ synaptoxicity is Dkk1-dependent 12 , 24 and also appears to be APP-dependent 25 . The results described above show that APP enhances the effects of Dkk1, changing the balance of Wnt signalling away from the Wnt-β-catenin pathway and towards Wnt-PCP signalling.…”
Section: Resultsmentioning
confidence: 98%
“…Increased expression of Dkk1 has been shown in post-mortem AD brain and in animal models of Aβ pathology 11 , and its expression is induced in neuronally enriched cultures as an early response to Aβ 10 . Dkk1 drives multiple aspects of Aβ-mediated neurotoxicity, including synapse loss through effects on Wnt signalling 12 14 . Dkk1 is known principally as an inhibitor of the Wnt-β-catenin, or canonical Wnt, pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential molecular mechanisms linking Aß and tau to synapse and circuit dysfunction include calcium dysregulation and calcineurin activation, which are known to contribute to Aß toxicity and spine collapse in vitro and in vivo and have recently been linked to tau mediated synapse impairment (Hudry et al, 2012;Kuchibhotla et al, 2008;Mattson et al, 1992;Wu et al, 2010;Yin et al, 2016;Zempel et al, 2010). Abnormal activation of synaptic receptors by Aß has also been shown to induce activation of kinases including Fyn and GSK3-ß which affect tau phosphorylation and synapse collapse (Ittner et al, 2010;Lovestone et al, 2014;Marzo et al, 2016;Purro et al, 2012;Roberson et al, 2011;Sellers et al, 2018;Small and Duff, 2008). Our RNAseq results add to the literature implicating cellular prion protein at the interface between Aß and tau as increases in PrPc mRNA in MAPT-AD mice was the largest change observed with RNAseq and these levels recover with tau suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, however, suggested that Rhoc did not play a significant role in microglia proinflammatory activation and microglia-induced neurotoxicity. In this context, ROCK inhibition by Y27632 or fasudil attenuates microglia activation, promoting some functional recovery in animal models for different neurological conditions (Mueller et al, 2005, Chen et al, 2013, Chong et al, 2017, Sellers et al, 2018. Because Rhoa is likely to exert its control over microglia immune activity through several other downstream effectors besides ROCK, which activation can also be regulated independently of Rhoa (Julian and Olson, 2014), these studies are not very informative concerning Rhoa regulation of microglial function.…”
Section: Discussionmentioning
confidence: 99%